Expanding Culturomics from Gut to Extreme Environmental Settings - Utkarsh Sood (American Society for Microbiology, 2021)
With the advent of metagenomics, a quest began to identify the dynamics of the microbial communities in different ecological niches. Altogether, this has resulted in identification of microorganisms but is limited to only a small number of phylogenetic groups that can be easily cultured.